ASPEK HUKUM CREDIT UNION DI INDONESIA - Maria Ana Liwa (Sekolah Tinggi Ilmu Hukum Awang Long, 2017)
Credit Union is a collection of people agree to form a company or a financial institution as a source of shared capital. With the capital of its shortcomings, these people invest, lend and develop money among themselves, with interest worthy of productive interest in order to achieve welfare and financial freedom (financial) together. The existence of Credit Union is to improve and provide quality of life for its members through the products and services (services) should the country in this case the government supports by providing adequate regulations or regulations as a legal umbrella. In Indonesia, the legal basis used for Credit Union is Article 33 of the 1945 Constitution of the Republic of Indonesia, and Law of the Republic of Indonesia Number 25 Year 1992 on Cooperatives and Government Regulation of the Republic of Indonesia No. 9 Year 1995 on the Implementation of Business Savings and Loans by Cooperatives.